Seaweed a sustainable and functional broiler feed additive: Meta-analysis of effects on performance and efficiency - Yousaf, Muhammad Rizwan; Ahmed, Bilal; Pandupuspitasari, Nuruliarizki Shinta; Setiaji, Asep; Khan, Faheem Ahmed; Lestari, Dela Ayu; Ali, Azhar; Ahmad, Hasan Moftah Ahmed; Pratama, Anugrah Robby; Sholikin, Mohammad Miftakhus; Raza, Muhammad Asif; Agusetyaningsih, Ikania; et al. (Journal of Advanced Veterinary Research, 2025)
The poultry industry constantly seeks sustainable and cost-effective solutions to enhance broiler growth performance and feed efficiency. Seaweed, a marine alga, has gained increasing attention as a potential natural feed additive for livestock, including poultry. This meta-analysis aimed to systematically evaluate the effects of seaweed supplementation on broiler chicken performance, specifically body weight gain (BWG) and feed conversion ratio (FCR). A comprehensive literature search was conducted (NCBI, Scopus, WOS, and Google Scholar) to identify relevant studies and 34 studies with 159 unique observations were included in this meta-analysis using OpenMEE Software. The pooled analysis revealed a significant positive impact of seaweed supplementation on both BWG and FCR. The results suggested that seaweed, particularly species (Kappaphycus alvarezii and Chondrus crispus) rich in bio-active compounds like polysaccharides and polyphenols, can enhance broiler growth and feed efficiency. Breed-specific responses suggest that Ross 308 and Arbor Acres showed the greatest performance under seaweed supplementation. The underlying mechanisms of action for increased performance include increase in beneficial microbiome diversity and enhanced immunity. Future research should focus on standardizing supplementation protocols, exploring bio-active compound mechanisms, and addressing long-term impacts.